Production and Characterization of 3-Methacryloxypropyltrimethoxysilane Modified Polyvinyl Acetate Dispersion - Mindaugas Dubininkas; Gintaras Buika (Kemija u Industriji, 2016)
Semi-continuous vinyl acetate (VAc) radical emulsion polymerization in water with 3-methacryloxypropyltrimethoxysilane (GF31) co-monomer was performed using protective colloid PVA and surface-active compound. The impact of GF31 on polyvinyl acetate (PVAc) dispersion physicochemical and production parameters were determined. Even low quantities of GF31 (up to 1.5 % of VAc mass) had crucial impact on PVAc dispersion and dispersion film’s parameters.